THE EFFECT OF SMOKING BEHAVIOR ON STROKE CASES IN SURABAYA CITY - Erren Silvia Herdiyani; Kurnia Dwi Artanti; Santi Martini; Sri Widati; Hario Megatsari; Muhammad Azis Rahman (Jurnal Berkala Epidemiologi, 2022)
Background: Stroke is a disease condition caused by the sudden stopping of the blood supply to the brain, either because of a blockage or ruptured blood vessels. The prevalence of stroke in Indonesia based on Basic health research in 2013 was 7‰ and increased in 2018 to 10.9‰. Purpose: This research aims to determine the effect of smoking behaviour on the prevalence of stroke in Surabaya, Indonesia. Methods: It was a cross-sectional study. The study population included all visitors to nerve poly at Haji Hospital Surabaya. Data were collected from respondents through interviews and patient medical record data from August to September 2019. Univariate and bivariate analyses were done to identify the association between smoking and stroke incidence. Results: A total of 187 people participated in the study. The majority of them were aged ≥ 55 years (78.16%), with 55.17% being male. There is 32.18% active smoker and 28.74% passive smoker for stroke patients. There is an association of the type of non-filter cigarettes with the prevalence of stroke p = 0.01, PR = 4.02; 95% Cl = 1.38-11.67), and duration of exposure ≥30 years (p = 0.01, PR = 7.84; 95% Cl = 2.75-22.32) Conclusion: there is an influence of types of non-filter cigarettes and exposure time ≥ 30 years with the incidence of stroke in the city of Surabaya.